2019
DOI: 10.1088/1361-6455/ab1a50
|View full text |Cite
|
Sign up to set email alerts
|

Tunable subluminal and superluminal light with optomechanical-induced transparency under steady-state configuration

Abstract: We study a two-cavity optomechanical system in which one cavity (A) encloses a mechanical resonator and the other cavity (C) encloses a two-level atom are, respectively, driven by a strong pump and a weak probe fields. In addition to a direct pathway, the excitations in cavity C and the enclosed atom can also be caused through an indirect pathway. The interference between the two possible routs for excitations produces a controllable transparency window in the probe transmission spectrum of cavity C. The coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Zhang et al [54] presented double OMIT in a compound optomechanical system due to the linear and quadratic coupling between the cavity and the membrane. Khan et al [58] recently reported controllable OMIT in a two-cavity optomechanical system due to the interference between the two possible routs for excitations. Liao et al [59] investigated OMIT in a hybrid optomechanical system with Kerr medium which could be tuned from slow light to fast light.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [54] presented double OMIT in a compound optomechanical system due to the linear and quadratic coupling between the cavity and the membrane. Khan et al [58] recently reported controllable OMIT in a two-cavity optomechanical system due to the interference between the two possible routs for excitations. Liao et al [59] investigated OMIT in a hybrid optomechanical system with Kerr medium which could be tuned from slow light to fast light.…”
Section: Introductionmentioning
confidence: 99%